2021
DOI: 10.1177/00220574211016397
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Technology for Teaching: The Use of a Mobile/Tablet Approach for Enhancing Students’ Learning (Design Interaction) Technology-Enhanced Learning (TEL)

Abstract: In industrial design education, the curriculum should be structured to facilitate and advance student learning. The purpose of this work is to enhance the education by introducing mobile lectures and imbedded innovative approach to Bournemouth University (BU) Education, which will be employed by the lecturer in the years to come.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
1
4
0
1
Order By: Relevance
“…Our findings resonate with prior research conducted by [ 6 , 17 , 29 , 54 , 56 , 63 ]. These studies collectively endorse the notion that ST can indeed impact AS in educational settings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings resonate with prior research conducted by [ 6 , 17 , 29 , 54 , 56 , 63 ]. These studies collectively endorse the notion that ST can indeed impact AS in educational settings.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have focused on the effect of technology integration on student engagement and motivation, which are key components of AE. [ 29 ] investigated the impact of mobile technology on student motivation in language learning and found that mobile applications and interactive activities enhanced students’ engagement and motivation. Similarly, [ 30 ] explored the effects of a mobile learning initiative on student engagement and reported positive outcomes, with students expressing increased motivation and interest in the language learning process.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Design thinking has a huge impact in encouraging the quality of education. TPACK-integrated Design Thinking has a positive impact on education in various countries (Tramonti & Dochshanov, 2023;Gashoot et al, 2021). Design thinking models that are commonly used are DSchool (40%) and IDEO (15%).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as mentioned by authors [41][42][43], mobile learning, as part of the inclusion of technology in education, is based on the internal motivation of the teacher to innovate in his or her teaching practices.…”
Section: Discussionmentioning
confidence: 99%